Pharmacists' Perspectives on Prescribing and Expanding Access to Hormonal Contraception in Pharmacies in the United States. (April 2021) - Rafie, Sally; Cieri-Hutcherson, Nicole E.; Frame, Tracy R.; Griffin, Brooke; Harris, John Brock; Horlen, Cheryl; Shealy, Kayce; Stein, Amy Buros; Stone, Rebecca H.; Vest, Kathleen; Westberg, Sarah; Yancey, Abigail M.
Introduction: Pharmacist prescribing of contraception is becoming increasingly available in selected states. The objective of this study was to assess US community pharmacists' perspectives on expanding access, barriers, and facilitators since states have begun pharmacist scope of practice expansions for prescribing contraception. Methods: A survey study of US community pharmacists' support for expanded access models, pharmacist prescribing practices and interest, and importance of safety, cost, and professional practice issues for prescribing was conducted. Results: Pharmacists are generally supportive of pharmacist prescribing and behind-the-counter models for hormonal contraception and generally opposed to over-the-counter access. A majority (65%) are interested in prescribing hormonal contraception. The top motivation for prescribing contraception is enjoying individual patient contact (94%). Safety concerns (eg, patients not obtaining health screenings) remained most important for pharmacist implementation, followed by cost (eg, lack of payment or reimbursement for pharmacists' services), and professional practice (eg, pharmacist time constraints and liability) issues. Conclusion: This study provides an updated understanding of attitudes toward models of expanded access to hormonal contraception, interest in prescribing, and barriers and facilitators to this service among community pharmacists. Many barriers such as time and reimbursement remain unchanged. This information can inform policy and implementation efforts.